1985
DOI: 10.1242/jcs.1985.supplement_3.5
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor receptors

Abstract: SUMMARYThere are two types of insulin-like growth factor (IGF) receptors. The type I receptor generally binds IGF-I more tightly than IGF-II and also interacts weakly with insulin. The type II receptor prefers IGF-II over IGF-I and does not recognize insulin. The type I receptor is made up of an alpha binding subunit (Mr 130000) and a beta subunit (Mr 95 000) probably organized as a heterotetramer (Oizfh)■ The type II receptor consists of a single binding unit (Mr 250000). IG F stimulates phosphorylation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 55 publications
0
49
0
1
Order By: Relevance
“…The IGF-I receptor mediates most of the biologic actions of both IGF-I and IGF-II (Cohick and Clemmons 1993), including the mitogenic, metabolic, and cellsurvival properties of IGFs through tyrosine kinase signaling activity. The IGF-II/mannose 6-phosphate receptor appears to be a bifunctional receptor serving as both a lysosomal enzyme-targeting system and a suppressor of the action of IGF-II by increasing its degradation (Nissley and Lopaczynski 1991;Oates et al 1998). The levels of IGF-I receptors in leiomyomas have been reported to exceed those of the myometrium in three studies (Chandrasekhar et al 1992;Tommola et al 1989; Van der Ven et al 1997), whereas Chandrasekhar et al found no difference in the levels of the IGF-II receptors.…”
Section: Growth Factors Identified In Fibroidsmentioning
confidence: 98%
“…The IGF-I receptor mediates most of the biologic actions of both IGF-I and IGF-II (Cohick and Clemmons 1993), including the mitogenic, metabolic, and cellsurvival properties of IGFs through tyrosine kinase signaling activity. The IGF-II/mannose 6-phosphate receptor appears to be a bifunctional receptor serving as both a lysosomal enzyme-targeting system and a suppressor of the action of IGF-II by increasing its degradation (Nissley and Lopaczynski 1991;Oates et al 1998). The levels of IGF-I receptors in leiomyomas have been reported to exceed those of the myometrium in three studies (Chandrasekhar et al 1992;Tommola et al 1989; Van der Ven et al 1997), whereas Chandrasekhar et al found no difference in the levels of the IGF-II receptors.…”
Section: Growth Factors Identified In Fibroidsmentioning
confidence: 98%
“…The specific importance of type II IGF receptors for cells of the glial lineage is suggested by the presence of high levels of this receptor, but not of type I IGF receptors, in a human glioblastoma cell line (Laurenzi et al, 1995) and by the preferential endocytosis of IGF-IH by rat neonatal astrocytes (Auletta et al, 1992). In most other systems, the type I IGF receptors mediate the mitogenic effect of both IGF-I and IGF-II (Nissley and Lopaczynski, 1991), and aIR3 generally inhibits IGF-I-stimulated growth (Nissley and Lopaczynski, 1991; Van der Ven et al, 1993b). However, the type H IGF receptor has been implicated as a mediator of IGFinduced growth-stimulatory effects in other models (reviewed in Nissley and Lopaczynski, 1991;additional observations in Mathieu et al, 1990, De Leon et al, 1992and Fournier et al, 1993.…”
Section: Igf-i-stimulated Proliferationmentioning
confidence: 99%
“…In most other systems, the type I IGF receptors mediate the mitogenic effect of both IGF-I and IGF-II (Nissley and Lopaczynski, 1991), and aIR3 generally inhibits IGF-I-stimulated growth (Nissley and Lopaczynski, 1991; Van der Ven et al, 1993b). However, the type H IGF receptor has been implicated as a mediator of IGFinduced growth-stimulatory effects in other models (reviewed in Nissley and Lopaczynski, 1991;additional observations in Mathieu et al, 1990, De Leon et al, 1992and Fournier et al, 1993. We found that 3-galactosidase, but not aIR3, completely inhibits IGF-Istimulated growth in G47 cells.…”
Section: Igf-i-stimulated Proliferationmentioning
confidence: 99%
“…Both IGFs can bind to the type I IGF receptor with similar affinity, whereas the type II IGF/mannose 6-phosphate receptor preferentially binds IGF-II. The type I IGF receptor mediates the mitogenic action of both IGFs (Nissley and Lopaczynski, 1991), and the type II IGF receptor is mainly associated with differentiation and histomorphogenesis (Nissley and Lopaczynski, 1991). IGF functions are modulated by IGF-binding proteins (IGFBPs), of which six distinct variants have been characterized (Drop et al, 1992).…”
mentioning
confidence: 99%